2022
DOI: 10.3390/nano12050814
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Gold Nanoparticles against Drug-Resistant Nosocomial Fungal Pathogens and Their Extracellular Enzymes: Resistance Profiling towards Established Antifungal Agents

Abstract: Drug resistance of filamentous fungi to the commonly used antifungal agents is a major concern in medicine. Therefore, an effective approach to treat several opportunistic fungal infections is the need of the hour. Mentha piperita is used in home remedies to treat different disorders. Isolates of fungi were taken from hospitals in Riyadh, Saudi Arabia, and identified using molecular tools. Amphotericin B, Voriconazole, and Micafungin were applied to screen the resistance of these isolates using both disc and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…One class of nanoparticles are solid lipid nanoparticles (SLNs) and nanostructured lipid carriers that improve lipid permeability and stability and allow the co-delivery of several drugs. However, they have the disadvantage of low drug loading capacity and drug expulsion during storage [ 155 , 164 ].…”
Section: Future Perspectives and Challenges Related To The Use Of Ant...mentioning
confidence: 99%
See 1 more Smart Citation
“…One class of nanoparticles are solid lipid nanoparticles (SLNs) and nanostructured lipid carriers that improve lipid permeability and stability and allow the co-delivery of several drugs. However, they have the disadvantage of low drug loading capacity and drug expulsion during storage [ 155 , 164 ].…”
Section: Future Perspectives and Challenges Related To The Use Of Ant...mentioning
confidence: 99%
“…Another study with nanometals was realized by Almansob et al [ 164 ]; this study evaluated the use of gold nanoparticles (AuNPs) synthesized from an extract of Mentha piperita to treat fungal infections. The results showed that these nanoparticles did not have a particularly effective antifungal effect against multidrug-resistant species of Aspergillus.…”
Section: Future Perspectives and Challenges Related To The Use Of Ant...mentioning
confidence: 99%
“…The use of physicochemical techniques [23–25] is limited due to the deployment of dangerous chemicals and their harmful impact on human health; biosynthesis has garnered much attention as this strategy delivers rapid economic results with less impact on human health [26–28] and the environment [29–31]. Green synthesis methods [32] are among the ideal methods applied for the production of nanoparticles because they are harmless [33], cheap [34], and simple [35, 36]. One of the significant nanotechnological research focuses on synthesizing M/MO NPs such as silver [37, 38], carbon [39, 40], zinc oxide [41–43], gold [44–46], copper [47–49], nickel [50–52], selenide [53], palladium [54, 55], molybdenum [56, 57], tin oxide [58], titanium [59], and iron [60, 61].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is an interdisciplinary knowledge of various disciplines [ 3 , 4 ], including physics [ 5 , 6 ], materials [ 7 , 8 , 9 ], engineering [ 10 , 11 , 12 ], mechanical engineering [ 13 , 14 , 15 , 16 ], agriculture [ 17 ], energy [ 18 , 19 , 20 ] and biology [ 21 , 22 , 23 , 24 , 25 ]. Recently, nanoparticles have been successfully used for sustained drug release [ 26 ], photo‐catalytic [ 27 , 28 , 29 ], degradation [ 30 , 31 , 32 , 33 , 34 ], detection [ 35 , 36 , 37 , 38 , 39 ], treatment of infections [ 40 ], and in the food industry as potent anti‐oxidant [ 41 , 42 ], larvicidal [ 43 ], antifungal [ 44 ] and antibacterial agents [ 45 , 46 ]. Various methods for producing nanoparticles are classified into three general methods: physical, chemical, and biological [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%